Islamic Character Education in Indonesian Elementary Schools: Its Role in Students’ Moral Development - Suradi, Ahmad; Afriyani, Lilis; Dwiyanti, Marsella Sri (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to analyze the role of Islamic character education in the moral development of elementary school students. The background of this research is grounded in the importance of character formation from an early age as a response to the moral crisis among the younger generation. Islamic character education is considered relevant because it is based on the values of the Quran and Sunnah, which shape personality holistically. This study employs a qualitative approach with a library research type combined with descriptive analysis. Data were obtained from books, scientific journals, and educational policy documents, then analyzed using content analysis techniques to examine the relationship between the concept of Islamic character education and children’s moral development. The results indicate that Islamic character education plays an important role in shaping students’ morality through the internalization of moral values encompassing relationships with Allah, fellow human beings, and the environment. Effective implementation integrates the aspects of moral knowing, moral feeling, and moral action, thereby optimizing the child’s innate potential (fitrah) and forming individuals of noble character.